1998
DOI: 10.1073/pnas.95.11.6061
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing leptin response by preventing SH2-containing phosphatase 2 interaction with Ob receptor

Abstract: Leptin is an adipocyte-derived cytokine that regulates food intake and body weight via interaction with its Ob receptor (ObR). Serum leptin levels are chronically elevated in obese humans, suggesting that obesity may be associated with leptin resistance and the inability to generate an adequate ObR response. Evidence suggests that transcriptional activation of target genes by STAT3 (signal transducer and activator of transcription) in the hypothalamus is a critical pathway that mediates leptin's action. Herein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
122
3
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(142 citation statements)
references
References 41 publications
11
122
3
4
Order By: Relevance
“…Further studies found that CNTF and leptin activate overlapping signaling molecules, notably the STAT3 transcription factor (9)(10)(11)(12)(13), and that, like ObR, CNTF receptors are located in hypothalamic nuclei involved in feeding (14). Consistent with this, CNTF mimics the ability of leptin to cause preferential loss of fat in mice that are obese because of genetic deficiency of leptin (ob͞ob mice) (14).…”
mentioning
confidence: 52%
“…Further studies found that CNTF and leptin activate overlapping signaling molecules, notably the STAT3 transcription factor (9)(10)(11)(12)(13), and that, like ObR, CNTF receptors are located in hypothalamic nuclei involved in feeding (14). Consistent with this, CNTF mimics the ability of leptin to cause preferential loss of fat in mice that are obese because of genetic deficiency of leptin (ob͞ob mice) (14).…”
mentioning
confidence: 52%
“…Tyrosine phosphorylation of IRS proteins has been shown to modulate after changes in serine phosphorylation of the proteins (22,23); however, this possibility also seems unlikely, because serine phosphorylation usually results in decreased mobility of IRS proteins on SDS͞PAGE and such decreased mobility did not occur after leptin prestimulation. The SH2 domain containing phosphatase SHP-2 has been implicated in leptin's action as well as in the dephosphorylation of IRS proteins (43)(44)(45); however, no changes in IRS-1-or IRS-2-associated SHP-2 could be identified after leptin treatment (data not shown). It is possible that leptin modifies the intracellular trafficking of the IRS proteins, changing the rates of phosphorylation and dephosphorylation (39).…”
Section: Discussionmentioning
confidence: 80%
“…We showed that phosphorylated Tyr 985 mediates association with SHP-2 during LRb signaling and functions upstream of ERK activation and c-fos transcription but does not inhibit acute leptin signaling. Others have suggested that SHP-2 acts as an inhibitor of LRb signaling by binding to Tyr 985 and dephosphorylating Jak2, STAT3, and LRb (27,28). In order to determine whether the differences among our data and those of others reflected the duration of the assay, we measured the ability of the wild-type and mutant ELR chimeras to stimulate transcription from a STAT3-responsive GAS-luciferase reporter plasmid during brief (6 h) and prolonged (24 h) stimulation ( Fig.…”
Section: Increased Signaling By Elrmentioning
confidence: 99%
“…Once in the nucleus, STAT3 mediates gene transcription, including transcription of the suppressor of cytokine signaling, SOCS3 (21,26). Phosphorylated Tyr 985 of LRb recruits the SH2 domain-containing protein-tyrosine phosphatase SHP-2 (21, 27,28). We have previously shown that Tyr 985 regulates ERK activation and c-fos transcription in cultured cells but does not alter phosphorylation of Jak2 or STAT3 during brief ligand stimulation (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation